58 Hospitalisation Rates and Causes for People with Dementia in Northern Ireland. (16th September 2019) - Zafeiridi, Evi; McMichael, Alan; McGuinness, Bernadette
Abstract: Background: People with dementia are almost 50% more likely to have an acute hospital admission due to a common age-related illnesses, such as urinary tract infection. They also have an 18% higher rate of readmission following discharge and approximately one quarter of hospital beds are occupied by people with dementia. Furthermore, people with dementia have an increased mortality rate in hospital and for six months after discharge compared to age-matched controls. This study assessed the hospitalisation and re-hospitalisation rates for people with dementia in Northern Ireland, as well as exploring whether mortality rates increase during or following these hospitalisations. A secondary aim was to explore the causes of hospitalisations between people with dementia and a representative age-matched control group. Methods: Data from over 50, 000 people with dementia and the control group from national databases in Northern Ireland were retrospectively analysed. Results: The results showed that dementia does not affect hospitalisations; however, the number of hospitalisations can predict mortality in people with dementia. The most common causes for hospitalisation did not differ between the dementia and the control groups and included pneumonia, urinary tract infection and fractures. Conclusion: The results will inform health care professionals on whether a reduced number of hospitalisations increases life expectancy and may result in relieving some of the financial strain currently being experienced by the National Health Service.